Case report: Long-term clinical benefit of pyrotinib therapy following trastuzumab resistance in HER2-amplification recurrent mucinous ovarian carcinoma - Fang, Xiangming; Mou, Haibo; Ying, Xinxin; Hou, Xuehua; Wang, Luo; Wu, Ying; Yan, Naimeng; Guo, Lijie; Liao, Qin (Frontiers in Oncology, 2022)
Advanced or recurrent mucinous carcinoma of the ovary minimally responds to current cytotoxic treatments and has a poor prognosis. Despite multimodal treatment using chemotherapy and surgery, most patients ultimately progress and require palliative systemic therapy. Anti-HER2 therapy has been demonstrated to be an effective strategy for the treatment of HER2-positive breast cancer. However, the role of anti-HER2 therapy in ovarian cancer remains largely unknown. Here, we report the case of a young woman with FIGO Stage IIIc recurrent mucinous ovarian carcinoma (MOC) who developed trastuzumab resistance and disease progression following cross-treatment with trastuzumab combined with pertuzumab. HER2 amplification was discovered using next-generation sequencing (NGS). The patient then received bevacizumab, and pyrotinib plus capecitabine treatment, and achieved a long-term clinical benefit for 22 months. Pyrotinib is a potential treatment for MOC patients who are heavily pretreated and harbor a HER2 amplification. Our case may provide valuable treatment information for patients with advanced or recurrent MOC.